2006
DOI: 10.1136/jnnp.2005.072199
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine levels in multiple sclerosis

Abstract: Background: There is evidence that homocysteine contributes to various neurodegenerative disorders, and elevated plasma homocysteine levels have been observed in patients with multiple sclerosis (MS). Objective: To investigate if and why plasma homocysteine levels are increased in MS, and whether they play a role in the disease course. Methods: We compared plasma levels of homocysteine in 88 patients with MS and 57 healthy controls. In the MS group, 28 had a benign course, 37 were secondary progressive, and 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 36 publications
6
78
2
2
Order By: Relevance
“…Lindenbaum and colleagues have suggested that measurement of pHcy levels before and after treatment can be valuable for confirmation of a differential diagnosis of neuropsychiatric disorder in patients presenting with paresthesia, sensory loss, ataxia, and dementia [18]. A recent study that confirmed elevated pHcy levels in MS patients concluded that the finding is unlikely to be related to immune activation, oxidative stress, or deficiencies in vitamin B6, B12, or folate [19]. Other investigations also support the finding of elevated homocysteine levels in MS patients compared with healthy controls [20], [21] and [22].…”
Section: Discussionmentioning
confidence: 99%
“…Lindenbaum and colleagues have suggested that measurement of pHcy levels before and after treatment can be valuable for confirmation of a differential diagnosis of neuropsychiatric disorder in patients presenting with paresthesia, sensory loss, ataxia, and dementia [18]. A recent study that confirmed elevated pHcy levels in MS patients concluded that the finding is unlikely to be related to immune activation, oxidative stress, or deficiencies in vitamin B6, B12, or folate [19]. Other investigations also support the finding of elevated homocysteine levels in MS patients compared with healthy controls [20], [21] and [22].…”
Section: Discussionmentioning
confidence: 99%
“…Immobilization and lack of physical activity among patients with MS may also increase the risk of CVD. There is evidence that homocysteine plasma levels, a risk factor for CVD, may be higher in patients with MS [42][43][44] . Thrombogenic factors [26,42,45] and endothelial function [47] may also be altered in patients with MS. As mentioned, MS patients may have a healthier lifestyle after MS diagnosis, and cardiovascular risk factors may be identified and treated during frequent health care contacts, which may explain the attenuated cardiovascular risk during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Serum and cerebrospinal fluid folate levels in 293 patients (with MS, Alzheimer's type dementia, non-Alzheimer's type dementia or myelopathy) and 157 control subjects, did not show significant differences between the various groups [53,54]. However, it has been suggested that low or reduced levels of folate found in MS patients may be related to previous corticosteroid treatments [55].…”
Section: The Role Of Vitamin B9 (Folate) In Msmentioning
confidence: 99%